Germination rate is the significant characteristic determining coconut palm diversity - Harries, Hugh C. (Oxford University Press, 2012)
RATIONALE: This review comes at a time when in vitro embryo culture techniques are being adopted for the safe exchange and cryo-conservation of coconut germplasm. In due course, laboratory procedures may replace the options that exist among standard commercial nursery germination techniques. These, in their turn, have supplanted traditional methods that are now forgotten or misunderstood. Knowledge of all germination options should help to ensure the safe regeneration of conserved material. SCOPE: This review outlines the many options for commercial propagation, recognizes the full significance of one particular traditional method and suggests that the diversity of modern cultivated coconut varieties has arisen because natural selection and domestic selection were associated with different rates of germination and other morphologically recognizable phenotypic characteristics. The review takes into account both the recalcitrant and the viviparous nature of the coconut. The ripe fruits that fall but do not germinate immediately and lose viability if dried for storage are contrasted with the bunches of fruit retained in the crown of the palm that may, in certain circumstances, germinate to produce seedlings high above ground level. SIGNIFICANCE: Slow-germinating and quick-germinating coconuts have different patterns of distribution. The former predominate on tropical islands and coastlines that could be reached by floating when natural dispersal originally spread coconuts widely—but only where tides and currents were favourable—and then only to sea-level locations. Human settlers disseminated the domestic types even more widely—to otherwise inaccessible coastal sites not reached by floating—and particularly to inland and upland locations on large islands and continental land masses. This review suggests four regions where diversity has been determined by germination rates. Although recent DNA studies support these distinctions, further analyses of genetic markers related to fruit abscission and germination are recommended.